Reducing Reliance on Natural Resource Revenue and Increasing Subnational Tax Autonomy in Bolivia - Giorgio Brosio (Inter-American Development Bank (IDB), 2012)
This paper address options for restructuring the revenue system of Bolivias subnational governments, particularly prefectures, emphasizing reduction of dependence on natural resources and strengthening of subnational tax autonomy. The paper additionally identifies tax instruments or tax bases that could be assigned exclusively to regional governments or shared with the central government, assessing their main advantages and disadvantages through a simulation of revenue generation. The results show that several options exist for increasing the tax autonomy of local governments. The tax instruments proposed in this paper carry relatively low administrative costs. In fact, the taxes proposed would not require the establishment of new agencies but could be collected by existing agencies and, in the case of energy and fuel taxes, by producing and distributing firms.
Keywords: H21; H23; H24; H25; H26; H71; 330